Forager Mobility and Lithic Discard Probability Similarly Affect the Distance of Raw Material Discard from Source. Issue 4 (October 2021) - Lin, Sam C.; Premo, L. S.
Abstract : The neutral model of stone procurement developed by Brantingham (2003, 2006) provides a formal means to investigate the formation of lithic discard patterning under changing forager mobility conditions. This study modifies Brantingham's (2006) Lévy walk model to examine the influence of discard probability on the spatial distribution of raw material abundance. The model outcome shows that forager movement and tool discard probability have similar effects on the simulated patterns of raw material transport, so it is difficult—if not impossible—to differentiate the respective influence of the two factors from distance to source distributions alone. This finding of equifinality complicates the task of interpretating hominin mobility from archaeological distance to source data, particularly in settings such as the Middle-Upper Paleolithic transition, which is marked by an important reorganization in hominin lithic technology that may have affected stone tool discard probability.